Industrial Mindset of Education in Merdeka Belajar Kampus Merdeka (MBKM) Policy - Denny Kodrat (Perhimpunan Intelektual Muslim Indonesia, 2021)
Merdeka Belajar Kampus Merdeka (MBKM) program is one of the distinguished programs issued by the Ministry of Education and Culture. It is expected that the university students enhance soft and hard skills by joining one of eight suggested programs. Link and match was an initial policy in the 1990s while the MBKM program is improved. The study aims to uncover the industrial interest embedded in MBKM policy by reviewing the concepts and educational design in Indonesia. Library research towards the ideas was reviewed. Reputable journals and books were collected and overviewed while the critical concept of education was carried out as a tool of analysis. The theory of education addressed by Illich (2000), Walker (1981), and Nabhani (2001) was employed to trace the Industrialization of education in MBKM policy. The study shows that the industrial factors in MBKM policy are highlighted and strengthened by giving students the right to take a program and doing a credit transfer at the end of the program. The university and study program curriculum is focused on the need for the business and industrial world.